2020
DOI: 10.21608/ejhc.2020.119016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Management Program on Self-efficacy regarding Osteoporosis Risk among Diabetic Patients

Abstract: Background: Prevalence of osteoporosis is high among diabetes patients. Assessment of self-efficacy regarding osteoporosis risk as well as patient education should be included as part of the self-management of diabetes. Aim:To evaluate the effect of a selfmanagement program on self-efficacy regarding osteoporosis risk among diabetic patients. Methods:A quasi-experimental (pre-posttest) research design was conducted on 90 diabetic patients who admitted in the internal medicine department at Assiut university ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, the significant differences between participants were related to these three predictors and the CI levels across the value of 1, which could lack the significance of these factors in relation to the level of self-efficacy. On the other hand, a study conducted in China showed that the self-efficacy of exercises is correlated with young age [29], while another study conducted on menopausal women above 45 years old by Janiszewska et al (2017) showed that a long period of treatment is positively correlated with self-efficacy [30]. 2023), specific measures customized to specific circumstances are essential [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant differences between participants were related to these three predictors and the CI levels across the value of 1, which could lack the significance of these factors in relation to the level of self-efficacy. On the other hand, a study conducted in China showed that the self-efficacy of exercises is correlated with young age [29], while another study conducted on menopausal women above 45 years old by Janiszewska et al (2017) showed that a long period of treatment is positively correlated with self-efficacy [30]. 2023), specific measures customized to specific circumstances are essential [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…Less than one tenth of the researched subjects were divorced and single, according to the current study findings, while more than two thirds were married. According to Khalil et al (2020), who conducted a study at Assiut University Hospital titled Effect of Self-Management Program on Self-Efficacy Regarding Osteoporosis Risk Among Diabetic Patients, the study subjects were married, single, or divorced in 80%, 6.7%, and 6.7% respectively (12) .…”
Section: Discussionmentioning
confidence: 99%